Micropuncturing the Nephron - Vallon, Volker (2008)
To achieve the role of the kidney in maintaining body homeostasis, the renal vasculature, the glomeruli, and the various segments of the nephron and the collecting duct system have to fulfil very diverse and specific functions. These functions are dependent on a complex renal architecture and are regulated by systemic hemodynamics, hormones and nerves. As a consequence, to better understand the physiology of the kidney, methods are necessary that allow insights on the function of these diverse structures in the physiological context of the intact kidney. The renal micropuncture technique allows direct access to study superficial nephrons in vivo. In this review, the application of micropuncture techniques on the single nephron level is outlined as an approach to better understand aspects of glomerular filtration, tubular transport, and tubulo-glomerular communication. Studies from the author’s lab, including experiments in gene-targeted mice, are briefly presented to illustrate some of the approaches and show how they can further advance our understanding of the molecular mechanisms involved in the regulation of kidney function.